Correlation of plasma kisspeptin with total testosterone levels in smokeless tobacco and smoking tobacco users in a healthy cohort: A cross‐sectional study. (9th September 2019) - Shah, Syed Salman; Shah, Mohsin; Habib, Syed Hamid; Shah, Fawad Ali; Malik, Muhammad Omar
Abstract: Human infertility is a worldwide health issue and is the inability to conceive following twelve months of unprotected sexual intercourse. Consistent studies reiterated tobacco abuse to be an important risk factor which adversely effects male fertility. This study aims to determine the correlation of kisspeptin and total testosterone levels in smokeless tobacco, smoking tobacco users and healthy controls. A total of 180 subjects were selected using random sampling technique. Non‐fasting blood samples (5 ml) were drawn, and ELISA technique was used for the evaluation of plasma levels of kisspeptin and total testosterone. Total testosterone was found to be significantly high in smokers and smokeless tobacco users, while the level of kisspeptin was found to be significantly high in smokeless tobacco users only as compared to control group. Furthermore, the level of cholesterol was found to be significantly low, whereas HDL and triglycerides were found to be significantly high in smokeless tobacco users relative to control subjects. Findings of this study suggest that tobacco use has impact on HPG axis by affecting kisspeptin level. The increase in kisspeptin level can affect hypothalamic function leading to pituitary and gonadal dysfunction along with impairment of reproduction. The finding that smokeless tobacco significantly raises kisspeptin strengthens the idea that smokeless tobacco use has more potent effects centrally compared to smoking.